The Relationship between Clean Water Facilities and Healthy Latrines with the Incidence of Diarrhea in Morosi District, Konawe Regency - Kurnia Saputra, Rois; Azizi Jayadipraja, Erwin; Nirwan, Muhammad (Waluya The International Science of Health Journal, 2023)
Introduction : From 2020 to 2022 in Konawe Regency in 2020 there were 6,877 cases with a prevalence of 27/100,000 population, diarrheal disease in the population of all ages there were 2,319 cases with a prevalence of 9/100,000 population in all age groups in 2020. According to data, there are 1,151 cases with a prevalence of 5/100,000 population in 2021 at all ages from January to August. This study aims to study the factors of the occurrence of diarrhea associated with basic sanitation and vectors in Morosi sub-district, Konawe district. Method : This type of research is a quantitative study using a cross-sectional study survey design and a descriptive survey. The population in this study is the community in Morosi District, Konawe Regency. The population of household heads is 1,549 households. Sampling using Cluster Random Sampling with a total sample of 91 respondents. The statistical test used is the data normality test and the chi square test. Result : This study showed that clean water facilities were not associated with diarrhea (p = 1.245 <0.05), healthy latrines were associated with diarrhea (p = 0.00 > 0.05). Conclusion : Healthy latrines, garbage disposal facilities, waste water disposal facilities and the density of flies are factors associated with the incidence of diarrhea in Morosi District, Konawe Regency.